An examination timetabling framework of decision support system based on quadratic assignment problem - Muktar, Danlami
Generating examination scheduling is an important and recurring administrative activity in almost all education institutions. Creating a good examination timetable system that satisfies students, lecturers and the institution management is a very difficult task due to the limited resources. This limitation makes examination scheduling very difficult to handle. The purpose of this research is to construct a framework that can provide solution for a complex examination scheduling system of Decision Support System based on Quadratic Assignment Problems (QAP) model. The framework consist of five phases ; the first phase identifies the parameters that influence scheduling while the second phase is the assignment of the parameters. During this third phase, QAP model is enhanced in order to reduce the level of conflict at each level of assignment and a hyper-heuristic is applied to improve the assignment until an optimal solution is found. The fourth phase identifies more possible constraints while the final phase applies solution based on QAP for the best possible result. This framework ensure the institution management, lecturers and students' requirement are fulfilled, and all the resources are fully utilized. A prototype system was design and applied based on the examination data gathered from the academic department of University Sultan Zainal Abidin (UniSZA). The system is able to solve the hard constraints and optimized soft constraint which ensure no single student has to sit for two or more examinations at the same time. The sequence between subjects is also scheduled well distance from one another in the examination timetable. This system has been able to schedule examination for 6748 students from 9 faculties and 18programs with 424 courses within 10 days duration for first semester of 2014/2015 session. This research revealed all possible constraints associated with examination scheduling. The evaluation of system applicability reveals that it satisfies the target users. QAP model can be used to maximized the utilization of resources and avoid conflict in the examination timetable.